Simulation modelling of QoS enhancements in IEEE, 802. 11 networks and the effects of channel modelling - Mundangepfupfu, Tinotenda Leslie (Department of Electrical Engineering, 2015)
In this work the impact of the channel effects in modelling EDCA and DCF protocols of the IEEE 802.11 Medium Access Control (MAC) protocol on overall network performance is investigated.